The new Blackwell companion to the city - Bridge, Gary; Watson, Sophie (Wiley-Blackwell, 2011)
This book considers the state of the city and contemporary urbanisation from a range of intellectual and international perspectives. The most interdisciplinary collection of its kindProvides a contemporary update on urban thinking that builds on well established debates in the fieldUses the city to explore economic, social, cultural, environmental and political issues more broadlyIncludes contributions from non Western perspectives and cities.